Reflections about the teaching of Biology in pandemic times (Research, Society and Development, 2023)
The new coronavirus pandemic has impacted the closure of schools, more than 1.5 million students and 60.3 million teachers in 165 countries. Several states and municipalities in Brazil used the remote educational system in the COVID-19 pandemic period. In view of the above, this article opened the following question: What are the methods used in the teaching of biology by teachers in the midst of the COVID-19 pandemic? Thus, the objective of this article was to carry out a bibliographic research on websites, books, articles and magazines on the teaching of biology in the remote period due to the COVID-19 Pandemic. A literature review was carried out using Google Scholar databases in order to identify scientific articles, dissertations, theses and works, in order to locate works with the theme addressed in the research. It was observed that teachers in this scenario had difficulties. The lack of preparation for new pedagogical methods, including the use of information technology and digital communication, became more evident, especially for teachers accustomed to traditional teaching methodologies. According to the articles analyzed, it is clear that remote education has evidently shown that teachers need to be more committed to the expansion of digital technology learning through continuing education. It is necessary to guide teachers through continuing education, from their own experiences, that is, their opinion, their point of view, so that the trainer can expand their skills and shape their attitude towards the teaching-learning process.